Higher-order beliefs among professional stock market forecasters: some first empirical tests - Jesper Rangvid; Maik Schmeling; Andreas Schrimpf (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
A sizeable literature reports that financial market analysts and forecasters herd for reputational reasons. Using new data from a large survey of professional forecasters' expectations about stock market movements, we find strong evidence that the expected average of all forecasters' forecasts (the expected consensus forecast) influences an individual forecaster's own forecast. This looks like herding. In our survey, forecasters do not herd for reputational reasons, however. Instead of herding, we suggest that forecasters form higher-order expectations in the spirit of Keynes (1936). We find that young forecasters and portfolio managers, who in previous studies have been reported to be those who in particular herd, rely more on the expected consensus forecasts than other forecasters. Given that forecasters have no incentive to herd in our study, we conclude that our results indicate that the incorporation of the expected consensus forecast into individual forecasts is most likely due to higher-order expectations.
Keywords: G10; G15; G17; 330; Higher-order expectations; stock market forecasts; forecaster heterogeneity; Finanzanalysten; Börsenkurs; Erwartungstheorie; Herdenverhalten; Deutschland